A View of Corpus Linguistics and Language Teaching - Ana Clara Sánchez Solarte; Gabriel Vicente Obando Guerrero (Asociación Colombiana de Profesores de Ingles, 2017)
Corpus linguistics is a topic that language teachers, especially EFL teachers should know due to its many possibilities for language instruction. The purpose of this article is precisely to look at the relationship between corpus linguistics and teaching. To do so we will define and look at the historical background of corpus linguistics and some research examples, then the applications and potential limitations of CL will be addressed.